DNAX-activating protein 10 co-stimulation enhances the anti-tumor efficacy of chimeric antigen receptor T cells. (2nd January 2019) - Zhao, Ruocong; Cheng, Lin; Jiang, Zhiwu; Wei, Xinru; Li, Baiheng; Wu, Qiting; Wang, Suna; Lin, Simiao; Long, Youguo; Zhang, Xuchao; Wu, Yilong; Du, Xin; et al.
ABSTRACT: Chimeric antigen receptor (CAR) T cell immunotherapies have shown remarkable efficacy in treating multiple types of hematological malignancies but are not sufficiently effective at treating solid tumors. NKG2D is a strong activating receptor for NK cells and a co-stimulatory receptor for T cells. NKG2D signal transduction depends on DNAX-activating protein 10 (DAP10). Here, we introduced the cytoplasmic domain of DAP10 into the second-generation CARs M28z and G28z to generate M28z10 and G28z10, which target mesothelin (MSLN) and glypican 3 (GPC3), respectively. T cells expressing M28z10 or G28z10 showed enhanced and prolonged effector function against MSLN+ lung cancer or GPC3+ hepatocellular carcinoma cell lines in culture and secreted elevated levels of cytokines, including IL-2, IFN-γ, granzyme B, and GM-CSF. In addition, M28z10 CAR-T cells showed greater anti-tumor activity than those expressing M28z in both A549 cell line xenografts and human lung cancer patient-derived xenografts (PDX). Similarly, G28z10 exhibited higher efficacy in causing tumor regression than did G28z in hepatocellular carcinoma PDX. Therefore, our results show that DAP10 signaling contributes to the function of CAR-T cells in both lung cancer and hepatocellular carcinoma and can enhance the efficacy of CAR-T cells.